Arabic Language Program Management at Dar Al-Lughah Wal-Quran Institute - Busaka, Muhammad Farhan (Nurul Jadid University, 2023)
Management is the process of implementing planning, organizing, choosing, and monitoring its implementation to achieve the desired goals. The objectives of the management process, of course, must start from how to understand oneself as a director or head of the institute, about how to style or art to emphasize, how to have the ability and skills, and the strategies that are used to accelerate the implementation process to achieve this goal, which can ultimately manage the desired results efficiently and effectively. This research aims to describe and know the planning, organization, implementation, and evaluation in the management of the Arabic language program at the Dar Al-Lugha Wal-Quran Institute. The method used by the researcher is the qualitative method with a descriptive approach, and its results are as follows: 1) Planning, determining the curriculum, determining the goals, and appointing the activities of the Arabic language environment. 2) Organization. Division of work for the supervisor in teaching the Arabic language and coordinating the responsibility of the supervisor. 3) Implementation by implementing Arabic language activities such as memorizing vocabulary, Arabic conversation, and presenting the Arabic lecture. 4) Evaluation of the linguistic exam, meaning the oral test for all activities.